The Development of Animation-Based Learning Media on Students' Mathematical Literacy Ability - Aedil Akbar; Lisnasari Andi Mattoliang; Baharuddin; Suharti; Ahyani Mirah Liani (Universitas Serambi Mekkah, 2024)
This research aims to develop animation-based learning media on students' mathematical literacy abilities at MAN Bantaeng and evaluate its validity, practicality, and effectiveness. This research uses the ADDIE model consisting of analysis, design, development, implementation, and evaluation. Research instruments include validation sheets, student and teacher response questionnaires, student activity observation sheets, teacher ability observation sheets in managing learning, and mathematical literacy tests. The test subjects were 21 students. The validity of this media is in the very valid category. Practicality was assessed as very positive, with teacher responses reaching 86.11% and the teacher's ability to manage learning reaching 4.51 in the very high category. The results of the effectiveness analysis are included in the very positive category, with student responses reaching 86%, student activity during learning reaching 60% in the good category, and the level of completion of the mathematics literacy test reaching 66.67%. Thus, animation-based learning media can be used in learning because it meets the validity, practicality, and effectiveness criteria.